Formation of Would-be Agrarians’ Communication (Speaking) Skills in the Process of the Integrated Teaching of Humanities in Agrarian Higher Educational Establishments - Dziubata, Zoriana (Pedagogical Discourse, 2014)
The article investigates the ways to optimize the process of forming would-be agrarians’ communication skills by means of using integration methods when teaching Humanities. The effective performance of the tasks of modern agrarian politics needs highly qualified workers, who are not only specialists with well-formed professional competence, but specialists, who have well-developed communication skills needed for their effective interpersonal and professional communication in their native and foreign languages. The integration of Humanities is an effective way of the targeted formation of would-be agrarians’ communication skills, as it makes it possible to provide wider practice and application of such skills in the process of the professional training of such specialists and ensures the optimization of the process in terms of its effectiveness and training time. Having analyzed the peculiarities and the difficulties of forming would-be agrarians’ communication skills in higher educational establishments today, and having investigated the integrative potential of Humanities, we suggest using certain ways to optimize the educational forms and methods in order to form would-be agrarians’ speaking skills effectively and to make this process targeted and successful.